Eksplorasi Jenis Produk Hasil Hutan Bukan Kayu (HHBK) di Pulau Tidore - Rini Husen; Ramli Hadun; Asiah Salatalohy (Savana Cendana, 2023)
This study aims to determine the types of Non-Timber Forest Products (HHBK) products on Tidore Island and to determine their utilization. The method used in this research is the observation method (survey) with the research design being descriptive method and data collection procedures or data collection techniques namely observation, interviews, literature study, and documentation. This research was carried out in June-July 2022 in seven sub-districts, namely: Tomagoba, Soasio, Indonesiana, Gurabunga, Kalaodi, Doyado, and Jaya sub-districts. The results showed that there were 14 types of NTFP products on Tidore Island which were made by craftsmen and processors including Chairs, Tables, Yarn (natural dyes), Traditional dance attributes, Dipper, Baskets, Saloi, Nyiru (Susiru), Filters (Aya-aya ), caping (Tolu), coconut baskets (Bika), food box (besek), flower pots, and cinnamon. The use of NTFP product types by craftsmen and processors is as a livelihood and for daily needs in the form of handicraft products and beverage processing products with different forms of utilization that can be used by consumers and the public. Craftsmen and processors need a place and special attention from the government to distribute, support and promote the products they create, especially products from NTFPs on Tidore Island.